Social connections and participation among people with mild cognitive impairment: barriers and recommendations - Zhu, Di; Al Mahmud, Abdullah; Liu, Wei (Frontiers in Psychiatry, 2023)
Objective: Social connections and participation are essential for individuals with mild cognitive impairment (MCI) to prevent the progression of cognitive decline and enhance their overall well-being. However, existing research has primarily focused on environmental barriers, overlooking personal factors and the interconnected nature of these barriers. Moreover, there is a lack of understanding regarding social connections and participation challenges specific to people with MCI in low- and middle-income countries. Therefore, this study aimed to explore the barriers that hinder social connections and participation among people with MCI in China and investigate opportunities to design appropriate supportive interventions. Methods: Thirty-one people with MCI (13 males and 18 females; mean age = 82.74 years, SD=7.69; mean MoCA score = 21.26, SD = 2.44) and thirteen caregivers were recruited to attend focus groups. In addition, ten therapists were interviewed using a semi-structured interview guide. Focus groups and interviews were audio-recorded, transcribed, and analyzed using a framework analysis approach. Results: We found that the ability to build social connections among people with MCI is affected by mobility challenges, intensive grandparenting responsibilities, availability of suitable activities, and feelings of exclusion in a closed-minded community environment. Personal reasons, such as lower social efficacy, inability to find suitable social activities, and intensive family responsibilities, discourage people with MCI from social participation. The digital literacy of people with MCI depends on their motivation to learn and use digital tools; people with MCI who live in a community have a higher digital literacy than those living in care centers. The motivation to achieve digital literacy is affected by perceived benefits, costs of technology use, and social influence. Conclusion: Multidimensional initiatives are needed to address barriers to social connections, participation, and technology adoption among individuals with MCI. This includes organizing and engaging in social activities, promoting awareness and education on the importance of social participation, and exploring technology-based interventions to improve memory and storytelling abilities. These efforts can create a supportive environment and empower individuals with MCI to participate actively in social interactions, enhancing their overall well-being.